COMPUTERIZATION OF EDUCATION AS A TOOL OF UNIVERSITY TEACHER’S BASIC FUNCTIONS SUPPORT - Denysenko В.В. (Journal of Information Technologies in Education (ITE), 2015)
The intensive process of education computerization confronts modern educators a number of economic, technical, social, psychological and educational problems that need to be solved. The use of computer technology in educational process opens enormous opportunities for the development of cognitive abilities – from sensory and perceptual to speech and mental forms. In broad dissemination and use of technical aids, optical and acoustic techniques, programmed education, cinema, television, computer, the modern scientists and researchers see one of the main factors to enhance education and upbringing level both at regular and higher education institutions. Unfortunately, the process of the organic combination of technical and pedagogical sciences in terms of theory and practice introducing computer (multimedia) teaching aids is not as powerful as expected; and as it has been dictated by the needs of the modern society. The slow pace of computerization’s implementation of the learning process at high school has been caused by the reasons of different nature and scale. The main objective of the article is to highlight the problems of computer teaching aids using in teaching process at higher education institutions. The conducted analysis of studying computerization allowed us determining the impact and role in providing the university teacher’s basic functions. It has been established that the teacher is one of the management leading objects of educational and cognitive students’ activity and all its functions practically may have computer support.